Isolasi, Identifikasi, dan Karakterisasi Mikroorganisme (Bakteri, Jamur, dan Yeast) dari Fermentasi Ikan Bekasam dengan Teknik Pewarnaan Gram dan Pewarnaan Spesifik - Putri Rahmadani; Ardi Mustakim (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Fermentation of ikan bekasam is a traditional process that involves the activity of microorganisms to produce a product with distinct taste, aroma, and texture. This process includes various microorganisms, such as bacteria, fungi, and yeasts, that play a crucial role in the transformation of fish properties during fermentation. This study aims to isolate, identify, and characterize the microorganisms involved in the fermentation of ikan bekasam using Gram staining and specific staining techniques. The isolation process was carried out using selective media to grow microorganisms from the bekasam samples, including both the fish and the fermentation liquid. Microorganism identification was performed by observing colony morphology, microscopic characteristics, and biochemical reactions. Gram staining was used to differentiate between Gram-positive and Gram-negative bacteria, while specific staining techniques were employed to detect certain cellular structures that aid in the identification of microorganisms. The characterization of microorganisms included an analysis of their physiological and biochemical properties, such as their ability to produce enzymes or secondary metabolites that play a role in fermentation and the development of the characteristic bekasam flavor. The results of the study showed that ikan bekasam contains a variety of microorganisms, including lactic acid bacteria such as Lactobacillus spp. and Pediococcus spp., which play a primary role in fermentation by providing the characteristic sourness. In addition, yeasts such as Saccharomyces cerevisiae were found in the bekasam samples, contributing to the fermentation process. Fungi, such as Aspergillus spp., were also isolated, although their role in the fermentation of ikan bekasam is more limited. This study provides insights into the diversity of microorganisms involved in the fermentation of ikan bekasam and their potential applications in the food industry. These findings open up opportunities to optimize the fermentation process by utilizing these microorganisms to produce more consistent and high-quality bekasam. Future research could further explore the optimal conditions for improving the quality of this fermented product.